Kesalahan Ejaan Bahasa Indonesia dalam Naskah Dinas di Kantor-Kantor Desa Wilayah Perbatasan - Maria Rosalinda Talan; Rince Jalla Wabang (Jurnal Bahasa dan Sastra, 2022)
Reality reveals that official script writing in government institutions in various regions, including border areas, still deviates from the Indonesian spelling. If left unchecked, this will affect the pattern of language habits in the future. Hence, this study aims at describing the forms of misspellings and the factors that influence the occurrence of misspellings in official document. Sources of data were procured from official documents and staff at the village offices of East Miomafo District, North Central Timor District, East Nusa Tenggara Province as the border region between Indonesia and Timor Leste. The techniques applied in data collection were documentation and interviews, then the data were analyzed by employing a flow model. The outcome of the research figured out that the forms of spelling errors comprised errors in the use of letters (capitals and bold letters), errors in word writing (affixes, bound forms, combinations of words, prepositions, abbreviations, numbers and numbers, as well as errors in the use of punctuation marks (colons, commas, dashes, and slashes). Factors causing spelling errors in official document were the writer's lack of understanding of Indonesian spelling and following examples of existing fallacious manuscripts. Based on these findings, official script writers in every government agency should be able to minimize factors that cause errors spelling by studying and understanding Indonesian spelling so that it no longer follows the example of an erroneous official document.